Penggunaan Level Energi Dan Protein Yang Berbeda Terhadap Efisiensi Pakan, Pendapatan, Dan Income Over Feed And Chick Cost Pada Ayam Kampung Super Fase Pertumbuhan - Hamzah, Ibrahim (Mitra Sains, 2019)
The aim of study is to determine the optimal combination between energy and protein levels on feed efficiency, income and (IOFCC) Income Over Feed and Chick Cost of growth phase of super local chiken. The study was conducted in Kawatuna Village, Mantikulore Sub-district, Palu from April 17th to July 17th , 2017. This study used 192 old 1 Day Old Chick (DOC) super local chicken and designed in a Completely Randomized Design (CRD) within factorial design with two factors. The first factor is the metabolic energy consisted of two levels i.e EM1 (2800 kcal / kg) and EM2 (3000 kcal / kg). The second factor is four levels of protein ration ie P1 (18%); P2 (19%); P3 (20%); and P4 (21%). These two factors obtained 8 of treatment combination and repeated 4 times, so there are 32 experiment units. The variables observed were feed efficiency, income, and income over feed and chick cost. The analysis of variance result showed that the interaction between energy and protein produce no significant (P> 0,05) effect to all observation variables. Moreover energy and protein factor also produced no significant (P> 0,05). However a combination between 2800 kcal/kg ME and 18% protein is recommended as optimum diet formulation.